Initial growth of the yellow passion plants submitted to gibberellin - Santos, Carlos Alan Couto dos; Vieira, Elvis Lima; Peixoto, Clovis Pereira; Benjamim, Denis Alves; Santos, Cícera Régis Siqueira dos (Comunicata Scientiae, 2010)
It aimed to evaluate the effects of gibberellin action on the growth of yellow passion fruit, under foliar spray in different solutions of GA3. The experiment was conducted at the Laboratory of Plant Physiology and in the greenhouse of the Center for Agricultural, Environmental and Biological Sciences of UFRB. Seeds of yellow passion fruit (Passiflora edulis Sims f. flavicarpa Deg) and growth regulator gibberellin (4% GA3), at doses 0.5; 1.0; 2.0; 4.0 mL of gibberellin per liter of solution and distilled water as control. The seeds were sown in polyethylene bags with 15cm wide x 20cm long (capacity 2 kg) containing washed sand. It was initially placed four seeds per bag in each repetition. At 15 days after sowing (DAS) it was held thinning leaving one plant per bag. The experimental design was completely randomized with five treatments and four replications. At 40 DAS, plants were submitted to spraying with solutions of gibberellin for seven consecutive days. At 70 DAS it were recorded: length of root, stem and total (cm), number of leaves, dry weight of root, leaf, stem and total plant (g). Concentrations in the range between 90 and 100 mg GA3 L-1, given by foliar sprays, promote significant growth in stem length. The plant regulator, for concentrations in the range of 78 and 92 mg GA3 L-1, increases the dry weight of root, stem and total passion fruit plant.